2016
DOI: 10.1021/acs.analchem.6b02438
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Collagen/Cell Penetrating Hybrid Peptide as Nanocarrier in Targeting-Free Cell Selection and Uptake

Abstract: The effective delivery of therapeutics and imaging agents to a selected group of cells has been at the forefront of biomedical research. Unfortunately, the identification of the unique cell surface targets for cell selection remains a major challenge, particularly if cells within the selected group are not identical. Here we demonstrate a novel approach to cell section relying on a thermo-responsive peptide-based nanocarrier. The hybrid peptide containing cell-penetrating peptide (CPP) and collagen (COLL) doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Our previous results showed that the NIH 3T3 Swiss mouse fibroblasts, which are also adherent cells, do not exhibit endosomal entrapment of FITC-COL-CPP. 18,19 Additionally, we tested a different malignant adherent cell line, FaDu cells (squamous cell carcinoma of the pharynx); while the uptake efficiency of the FITC-COL-CPP follows the behavior of A549 cells (lower than Jurkat cells), we do not observe endosomal entrapment. The IC 50 of PTX-COL-CPP for FaDu cells was determined to be 0.58 ± 0.14 μM.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous results showed that the NIH 3T3 Swiss mouse fibroblasts, which are also adherent cells, do not exhibit endosomal entrapment of FITC-COL-CPP. 18,19 Additionally, we tested a different malignant adherent cell line, FaDu cells (squamous cell carcinoma of the pharynx); while the uptake efficiency of the FITC-COL-CPP follows the behavior of A549 cells (lower than Jurkat cells), we do not observe endosomal entrapment. The IC 50 of PTX-COL-CPP for FaDu cells was determined to be 0.58 ± 0.14 μM.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 92%
“…We have previously described this selection mechanism and showed that it can have a switch-like behavior that can potentially lead to complete lack of systemic toxicity. 19 The goal of this study is to conjugate paclitaxel to COL-CPP peptide carrier and evaluate its uptake and biological activity on representative cancer cell lines known to respond to PTX treatment. The peptides were synthesized and characterized using solid phase synthesis by Tufts Core Facility (commercially available).…”
mentioning
confidence: 99%
“…A number of strategies have been undertaken by the drug delivery community to bypass such resistance in an attempt to design efficient polymeric nanocarriers . These approaches include, but not limited to, using drug–polymer conjugates, immobilizing cell‐penetrating and targeting ligands on nanocarrier surface, designing systems that respond to a particular or a combination of microenvironmental abnormalities such as low pH or expression of a specific group of enzymes, using external stimuli such as thermal, biochemical, or magnetic field to guide accumulation of drug carriers at disease sites, to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, non-specific interactions with other anionic compounds, lack of adequate protection of the cargo against nucleases and proteases, and cytotoxicity, further complicate the use of CPP as carriers 13 . We have recently demonstrated that many of these challenges can be resolved by introducing architectural motifs via synthetic linking of CPP with a collagen peptide 15,16 . This resulted in the formation of a triple helical nanocarrier that effectively delivered Paclitaxel to malignant cells 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The folding motifs has been recently proposed as functional elements in drug delivery systems to introduce the conformational changes and supramolecular assembly as “actuators” to carry the intended biological function 21,22 . We have previously shown that the temperature induced peptide folding of hybrid peptides into higher order structure, triple helix, allows for control selection of cellular delivery 16 . The synthetic collagen peptides are also capable of forming hierarchical structures via self-assembly 2325 .…”
Section: Introductionmentioning
confidence: 99%